Comparison of Vegetation Indexes with Landsat images using cloud computing: Pampa de Majes-Siguas area, Arequipa-Peru (Period: Jun 1984 to Nov 2018) - Alvarado, Carlos (2019)
The objective of this work was to obtain vegetation indexes using the Landsat satellite images at the top of the atmosphere (TOA), the area of inuence of the Majes Authority Special Project (AUTODEMA), which covers the Pampas de Majes - Siguas, in Arequipa - Peru. From 1984 to 2018. For this purpose, the Cloud Engine cloud computing application was used in the Google Earth Engine (GEE) database, at the Petabyte (PB) scale. The tool called Climate Engine developed by researchers from the University of Idaho and Desert Research Institute - DRI was used. Allowing web processing satellite images of the Landsat Mission, extract values from the various bands, within a grid, to determine the Vegetation Indexes such as NDVI, NDWI, SAVI, GNDVI, obtaining a series of time within the study surface of the AUTODEMA and be able to estimate the amount and degree of development of the plant species planted and their impact on the use of water by means of transfer from the Camaná river basin to the Pampas de Majes-Siguas, expanding the agricultural frontier.